2007
DOI: 10.1200/jco.2006.10.4968
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Benefit With Docetaxel Plus Fluorouracil and Cisplatin Compared With Cisplatin and Fluorouracil in a Phase III Trial of Advanced Gastric or Gastroesophageal Adenocarcinoma: The V-325 Study Group

Abstract: To our knowledge, V325 is the first phase III trial to report clinical benefit in AGGEC patients. Clinical benefit was assessed beyond protocol-specific chemotherapy. The addition of D to CF not only significantly improved clinical benefit but also improved quality of life, time to progression, and overall survival compared with CF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
135
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(143 citation statements)
references
References 12 publications
5
135
0
3
Order By: Relevance
“…A total of 268 cycles (median, 5; range, [1][2][3][4][5][6][7][8][9][10][11][12][13][14] were administered in the 54 patients assessable for toxicity. The most frequently observed severe hematological adverse event was neutropenia, which occurred with grade 3 intensity in 14 patients (25.9%) and in 27 cycles (10.1%).…”
Section: Toxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 268 cycles (median, 5; range, [1][2][3][4][5][6][7][8][9][10][11][12][13][14] were administered in the 54 patients assessable for toxicity. The most frequently observed severe hematological adverse event was neutropenia, which occurred with grade 3 intensity in 14 patients (25.9%) and in 27 cycles (10.1%).…”
Section: Toxicitymentioning
confidence: 99%
“…Among the various active chemotherapeutic agents, cisplatin-based chemotherapy is the most commonly used worldwide. The V-325 study demonstrated that adding docetaxel (D) to a frequently used regimen of cisplatin and 5-fl uorouracil (CF) provided benefi ts with regard to overall survival, response rate, time to disease progression, clinical benefi t, and healthrelated quality of life [5]. Although the DCF regimen provides these advantages, it is accompanied by an increase in toxicity compared with the doublet regimen.…”
mentioning
confidence: 99%
“…Compared with the best supportive care, first-line chemotherapy for advanced gastric cancer (AGC) improves survival time and quality of life (2)(3)(4); however, the median overall survival (OS) time is short (9-13 months) (5)(6)(7). Several previous studies have demonstrated that second-line chemotherapy confers a significant survival benefit over best supportive care in AGC, with median OS time ranging from 4 to 9.5 months (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…The docetaxel (D)-cisplatin-5-FU (DCF) regimen has been shown to be superior to FP [10,11] in a phase III trial, with an improvement in time to progression (HR: 1.47), overall survival (OS) and quality of life. However, DCF has not been widely used because it is associated with a high rate of hematological toxicity, including grade 3-4 neutropenia (82 vs. 57 %) and complicated neutropenia (29 vs. 12 %).…”
Section: Introductionmentioning
confidence: 99%